Improving Learning Outcomes of Vegetative Plant Breeding Material Using Interactive Media for Grade VI Students of SDN 2 Kapungan - Anjar Budi Sulistiyo (Universitas Sebelas Maret, 2022)
The purpose of this study was to improve the learning outcomes of grade VI students of SD Negeri 2 Kapungan, Polanharjo District, Klaten Regency on the subject of vegetative plant reproduction in thematic learning. The learning media used in class action research conducted in thematic learning of grade VI SD Negeri 2 Kapungan, Polanharjo District, Klatena Regency is interactive media. This research is called classroom action research (PTK) because the researcher, who conducts the research is an educator in that place, while this research design uses a cycle, which consists of 2 learning cycles. The target of the research was the 6th grade students of SD Negeri 2 Kapungan, Polanharjo District, Klaten Regency with a total of 10 students (5 male, 5 female). The data collected was then processed using descriptive quantitative. Based on the above analysis, it can be concluded that the results of student learning completeness after using interactive learning media and approaches per cycle, student learning completeness is 100%, students feel enthusiastic in participating in learning with interactive learning media.